Antioxidant Activity of Porang (Amorphophallus muelleri) Leaves Ethanol Extract and Its Application as Cream Preparation - Willy Tirza Eden; Erlina Sari; Endah Widhihastuti; Tri Minarsih; Senda Kartika Rakainsa (Jurnal Kartika Kimia, 2026)
Antioxidants are compounds that can overcome the effects of free radicals. One of the plants that has antioxidant activity is the Porang plant (Amorphophallus muelleri). This study aims to determine the antioxidant activity of the Porang leaves’ ethanol extract and fraction using the DPPH method. Porang leaves were extracted using maceration with 96% ethanol and separated by fractionation using n-hexane and ethyl acetate. The ethanol extract and the three fractions were tested for their activity as antioxidants using the DPPH method with ascorbic acid as positive control. Phytochemical screening and Total Flavonoid Content (TFC) assay were also conducted. Phytochemical screening showed the presence of flavonoids, tannins/polyphenols, and terpenoids. Quantitative test for Total Flavonoid Content (TFC) showed that the greatest flavonoid content was found in the ethyl acetate fraction, which was 101.93 ± 2.75 mgQE/g. The results showed that the strongest antioxidant activity was possessed by ethanol extract (IC50 66.39 ± 0.44 µg/mL), followed by the ethyl acetate fraction (IC50 72.19 ± 4.37 µg/mL), ethyl acetate insoluble fraction (IC50 135.48 ± 2.54 µg/mL), and the weakest was n-hexane fraction (IC50 198.31 ± 16.75 µg/mL). Hence, cream was prepared using ethanol extract which possesses the strongest antioxidant activity. Formula 4 (7.5% extract) showed the strongest antioxidant activity (IC50 1,637.12 µg/mL), followed by formula 3 (5% extract) with IC50 of 2590.377 µg/mL, formula 2 (2.5% extract) with IC50 of 3,898.694 µg/mL, and formula 1 (cream base) with IC50 of 110,727.4 µg/mL. All cream formulations which contained porang leaves extract (F2 – F4) had higher antioxidant activity than formula 1 (base), although their antioxidant activity was classified as very weak.